Case Report: Auricular vagus nerve stimulation possibly alleviates COVID-19 disease on a high-risk patient - Széles, József Constantin; Lucny, Felix; Tyercha, Alexander; Kaniusas, Eugenijus; Neumayer, Christoph (Frontiers in Physiology, 2023)
Introduction SARS-CoV-2 is a highly contagious virus that was identified as the cause of COVID-19 disease in early 2020. The infection is clinically similar to interstitial pneumonia and acute respiratory distress syndrome (ARDS) and often shows cardiovascular damage. Patients with cardiovascular risk factors are more prone to COVID-19 disease and their sequelae. Due to the anti-inflammatory effect and the improvement in pulmonary function, auricular vagus nerve stimulation (aVNS) therapy might alleviate a COVID-19 infection. Patient and Methods A high-risk patient with cardiovascular diseases and implanted cardiac defibrillator (ICD), type 2 diabetes and PAD IV, according to Rutherford`s classification, became infected with COVID-19. The patient underwent wound surgery because of an infected necrosis with a methicillin-resistant Staphylococcus aureus (MRSA) of his small toe and was already on aVNS therapy to relieve his leg pain and improve microcirculation. AVNS was performed with the AuriStim device (Multisana©), which stimulates vagally innervated regions of the auricle by administering electrical stimulation via percutaneous electrodes for six weeks. Results The multimorbid high-risk patient, who was expected to go through a severe course of the COVID-19 disease, showed hardly any symptoms during ongoing aVNS therapy, while other family members, being much younger and healthy suffered from a more serious course with headache, pneumonia and general weakness. Conclusion The auricular vagus nerve stimulation is a clinically tested and safe procedure and might represent an alternative and effective way of treating COVID-19 disease.